Global economic prospects. (Online access: World Bank World Bank Open Knowledge Repository., 2015)
Global growth is expected to be 2.8 percent in 2015, but is expected to pick up to 3.2 percent in 2016-17. Growth in developing countries and some high-income countries is set to disappoint again this year. The prospect of rising borrowing costs will compound the challenges many developing countries are facing as they adapt to an era of low commodity prices. Risks to this outlook remain tilted to the downside. This edition of Global Economic Prospects includes two special features that analyze the policy challenges raised by the two transitions in developing countries: the risks associated with the first U.S. central bank interest rate increase since 2006 and the implications of persistently low commodity prices for low-income countries. Global Economic Prospects is a World Bank Group Flagship Report that examines global economic developments and prospects, with a special focus on developing countries, on a semiannual basis (in January and June). The January edition includes in-depth analyses of topical policy challenges faced by developing countries while the June edition contains shorter analytical pieces.